Designing an effective vaccine to prevent Epstein-Barr virus-associated diseases: challenges and opportunities. (3rd April 2017) - Dasari, Vijayendra; Bhatt, Kunal H.; Smith, Corey; Khanna, Rajiv
ABSTRACT: Introduction : Epstein-Barr virus (EBV) is a ubiquitous herpesvirus associated with a number of clinical manifestations. Primary EBV infection in young adolescents often manifests as acute infectious mononucleosis and latent infection is associated with multiple lymphoid and epithelial cancers and autoimmune disorders, particularly multiple sclerosis. Areas covered : Over the last decade, our understanding of pathogenesis and immune regulation of EBV-associated diseases has provided an important platform for the development of novel vaccine formulations. In this review, we discuss developmental strategies for prophylactic and therapeutic EBV vaccines which have been assessed in preclinical and clinical settings. Expert commentary : Major roadblocks in EBV vaccine development include no precise understanding of the clinical correlates of protection, uncertainty about adjuvant selection and the unavailability of appropriate animal models. Recent development of new EBV vaccine formulations provides exciting opportunities for the formal clinical assessment of novel formulations.